The First Human Vulvar Intraepithelial Neoplasia Cell Line with Naturally Infected Episomal HPV18 Genome - Ming Wu; Xiu Zhang; Yiyi Kang; Yaqi Zhu; Zhaoyu Su; Jun Liu; Wei Zhang; Hong Chen; Hui Li (Viruses, 2022)
Persistent infection with high-risk HPV leads to cervical cancers and other anogenital cancers and head and neck carcinomas in both men and women. There is no effective drug fortreating HPV infection and HPV-associated carcinomas, largely due to a lack of models of natural HPV infection and the complexity of the HPV life cycle. There are no available cell lines from vulvar, anal, or penile lesions and cancers in the field. In this study, we established the first human cell line from vulvar intraepithelial neoplasia (VIN) with naturally infected HPV18 by conditional reprogramming (CR) method. Our data demonstrated that VIN cells possessed different biological characteristics and diploid karyotypes from HPV18-positive cancer cells (HeLa). Then, we determined that VIN cells contained episomal HPV18 using approaches including the ratio of HPV E2copy/E7copy, rolling cycle amplification, and sequencing. The VIN cells expressed squamous epithelium-specific markers that are different from HeLa cells, a cervical adenocarcinoma cell line. When cultured under 3D air–liquid interface (ALI) system, we observed the expression of both early and late differentiation markers involucrin and filaggrin. Most importantly, we were able to detect the expression of viral late gene L1 in the cornified layer of ALI 3D culture derived from VIN cells, suggesting quite different HPV genomic status from cancer cells. We also observed progeny viral particles under transmission electron microscopy (TEM) in ALI 3D cultures, confirming the episomal HPV18 genome and active viral life cycle in the new cell line. To our knowledge, this is the first human VIN cell line with naturally infected HPV18 genome and provides a valuable model for HPV biology studies, HPV-associated cancer initiation and progression, and drug-screening platforms.